COMPOUND WORDS IN CHILDREN’S BOOKS TITLE AS A MEAN TO ACCELERATE CHILDREN VOCABULARY ACQUISITION - Dina Oktafiani; Retno Purwani Sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study deals with compound words in the children’s books title. It aims to identify the element constructing of compound words, to classify types of those, to determine the meaning conveying in children’s books title, and to learn how compound words can help children in enriching vocabularies. The technique used in data collection was the documentation method with note-taking techniques. As a qualitative descriptive, this study applied the descriptive technique to analyze classified data. The result of this study indicate that: (1) compound word constructions might consist of a noun, verb, and adjective; (2) three types of compound words are found in children's book titles, namely endocentric compounds, copulative compounds, and exocentric compounds; (3) the construction bring new concepts into words; and (4) construction, free morpheme with a new concept of meaning, enriching children's knowledge of the words